Hard miles [videorecording (DVD)] - Hanna, R.J. Daniel; Sander, Christian (Film producer); Modine, Matthew; McWilliams, Cynthia Kaye; Cuillory, Jahking (Filmhub, 2026)
A strong-willed social worker at a youth prison assembles a cycling team of teenage convicts and takes them on a transformative 1000-mile ride. Inspired by the life of Greg Townsend and the Ridgeview Academy Cycling Team.